International Physical Activity Questionnaire (IPAQ) and New Zealand Physical Activity Questionnaire (NZPAQ): A doubly labelled water validation - Rodgers Anthony; Vander Hoorn Stephen; Jiang Yannan; Ni Mhurchu Cliona; Maddison Ralph; Lawes Carlene MM; Rush Elaine (BMC, 2007)
Abstract Background Accurate measurement of physical activity is a pre-requisite for monitoring population health and for evaluating effective interventions. The International Physical Activity Questionnaire (IPAQ) is used as a comparable and standardised self-report measure of habitual physical activity of populations from different countries and socio-cultural contexts. The IPAQ has been modified to produce a New Zealand physical activity questionnaire (NZPAQ). The aim of this study was to validate the IPAQ and NZPAQ against doubly labelled water (DLW). Method: Total energy expenditure (TEE) was measured over a 15-day period using DLW. Activity-related energy expenditure (AEE) was estimated by subtracting the energy expenditure from resting metabolic rate and thermic effect of feeding from TEE. The IPAQ (long form) and NZPAQ (short form) were completed at the end of each 7-day period. Activity-related energy expenditure (IPAQAEE and NZPAQAEE) was calculated from each questionnaire and compared to DLWAEE. Results Thirty six adults aged 18 to 56 years (56% female) completed all measurements. Compared to DLWAEE, IPAQAEE and NZPAQAEE on average underestimated energy expenditure by 27% and 59%, respectively. There was good agreement between DLWAEE and both IPAQAEE and NZPAQAEE at lower levels of physical activity. However there was marked underestimation of questionnaire-derived energy expenditure at higher levels of activity. Conclusion Both the IPAQ and NZPAQ instruments have a demonstrated systematic bias toward underestimation of physical activity-related energy expenditure at higher levels of physical activity compared to DLW. Appropriate calibration factors could be used to correct for measurement error in physical activity questionnaires and hence improve estimation of AEE.